An assessment of facility readiness for comprehensive abortion care in 12 districts of Pakistan using the WHO Service Availability and Readiness Assessment tool - Palitha Gunarathna Mahipala; Sabeen Afzal; Qudsia Uzma; Atiya Aabroo; Nilmini Hemachandra; Katy Footman; Heidi Bart Johnston; Bela Ganatra; Tahira Ezra Reza; Ahsan Maqbool Ahmad; Hasan Bin Hamza; Maida Umar; et al. (Sexual and Reproductive Health Matters)
Although Pakistan’s Essential Package of Health Services was recently updated to include therapeutic and post-abortion care, little is known about current health facility readiness for these services. This study assessed the availability of comprehensive abortion care, and readiness of health facilities to deliver these services, within the public sector in 12 districts of Pakistan. A facility inventory was completed in 2020–2021 using the WHO Service Availability and Readiness Assessment, with a newly developed abortion module. A composite readiness indicator was developed based on national clinical guidelines and previous studies. Just 8.4% of facilities reported offering therapeutic abortion, while 14.3% offered post-abortion care. Misoprostol (75.2%) was the most common method provided by facilities that offer therapeutic abortion, followed by vacuum aspiration (60.7%) and dilatation and curettage (D&C) (59%). Few facilities had all the readiness components required to deliver pharmacological or surgical therapeutic abortion, or post-abortion care (<1%), but readiness was higher in tertiary (22.2%) facilities. Readiness scores were lowest for “guidelines and personnel” (4.1%), and slightly higher for medicines and products (14.3–17.1%), equipment (16.3%) and laboratory services (7.4%). This assessment highlights the potential to increase the availability of comprehensive abortion care in Pakistan, particularly in primary care and in rural areas, to improve the readiness of health facilities to deliver these services, and to phase out non-recommended methods of abortion (D&C). The study also demonstrates the feasibility and utility of adding an abortion module to routine health facility assessments, which can inform efforts to strengthen sexual and reproductive health and rights.